Impact of the 2023-2024 El Niño event on Ecuador’s insular region: rainfall response in the Galápagos Islands (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
This study documents the presence and evolution of the 2023-2024 El Niño event in Ecuador’s insular region based on precipitation data from meteorological stations M0221 (San Cristóbal - Galápagos), M0191 (Baltra), and M1236 (San Cristóbal - Airport), all operated by INAMHI. Conventional and automatic observations are integrated with spectral analysis using the wavelet transform and historical series dating back to 1964. The results show anomalous rainfall behavior at all stations, with monthly totals significantly exceeding the normal climatology (1981-2010) during the first quarter of 2024, reaching maxima of 282 mm in February and 267.7 mm in March. From May onward, a transition toward drier conditions is observed, coinciding with the weakening of the ENSO signal. Spectral analysis reveals a significant signal in the 2-8-year band, consistent with variability associated with ENSO. This work contributes to the regional characterization of ENSO in the eastern Pacific and underscores the importance of strengthening climate monitoring in the Galápagos, a strategic yet sparsely studied region due to its isolated geographic setting on the Equator. The findings are relevant for improving understanding of ENSO impacts in South America and for bolstering early warning systems in sensitive areas of the South Pacific.